The Role of Theology in Addressing Sustainable Development: Insights from Jamaluddin Al-Afghani's Thought - Sari, Melani Novita; Khairanisa, Mutia (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This study examines the theological thought of Jamaluddin Al-Afghani, focusing on its relevance to contemporary global challenges and sustainable development. Al-Afghani emphasized liberation, independence, and the active role of theology in societal progress, framing it as a solution-oriented discipline beyond mere ritual. Contextualized within the complexities of the modern era, particularly the United Nations' Sustainable Development Goals (SDGs), this research employs library research with a descriptive-analytical method and a philosophical-critical approach. Data sources include academic journals, theses, and scholarly works related to theology and Al-Afghani’s contributions. The findings reveal that Al-Afghani’s theological thought extends beyond ritualistic dimensions, offering practical solutions that inspire human agency, scientific advancement, and social justice. His ideas are universally applicable, promoting efforts to empower the marginalized and encourage the pursuit of knowledge for the betterment of society. The study contributes to academic discourse by demonstrating the relevance of Al-Afghani’s thought as a critical framework for addressing contemporary challenges, enriching the intersection of theology and sustainable development in both Muslim and global contexts.